P266 Elderly-onset Inflammatory Bowel Disease: a retrospective single-center study with current follow-up. (21st January 2022) - Dias, E; Nunes, A C R; Garrido, I; Andrade, P; Lopes, S; Macedo, G
Abstract: Background: Elderly-onset inflammatory bowel disease (IBD) will be seen more frequently with the ageing of the population and the increasing incidence of IBD. However, to date there are few studies focusing in the medical management of IBD in this patient population. The aim of our study was to describe the main clinical features of elderly-onset IBD. Methods: Patients diagnosed with IBD after the age of 65 years (elderly-onset IBD) until December 2020 with current follow-up in a specialized IBD consultation in a tertiary hospital center (by June 2021) were included in this retrospective study. The hospital electronic medical records were searched in order to retrieve demographic and clinical data of the patients. Results: A total of 61 patients were included, with mean age of 72.0 years (range 65–86); 34 (55.7%) were male. All patients were alive and with current follow-up. Mean follow-up duration was 84 months (interquartile range 35–97). The most common type was ulcerative colitis in 36 (59%) patients, whereas Crohn's disease was diagnosed in 25 (41%). Among patients with ulcerative colitis, 14 (38.9%) had pancolitis, 11 (30.6%) left-sided colitis and 11 (30.6%) proctitis. Crohn's disease was most often ileal in 48% of patients, followed by colonic in 44% and only 8% of patients presented ileocolonic disease. Non-stenosing non-penetrating behavior was present in 19 (76%) patients, followed by stenosing behavior in 6 (24%), with no case of penetrating phenotype; associated perianal disease was detected in 5 (20%) patients. Salicylates were used as single maintenance therapy in 44 (72.1%) of all patients with IBD; 11 (18%) patients required immunosuppressant therapy with biological agents including infliximab (n=5), vedolizumab (n=5) or ustekinumab (n=1) whereas 4 (6.6%) patients required no specific treatment. Surgery was necessary in only 3 (4.9%) patients: 2 performed total colectomy for refractory ulcerative colitis, whereas the other required right ileocolectomy for stenosing Crohn's disease. At the time of diagnosis, anemia was present in 23 (37.7%) patients. In 21 (34.4%), levels of C-reactive protein were significantly elevated (>10 mg/L) and hypoalbuminemia was present in 12 (19.7%). Vitamin D levels were measured in 44 patients, among these 41 (93.2%) presented abnormally low levels. Conclusion: Patients with elderly-onset IBD appear to have a mild disease course, with low use of biological agents and surgery. Ileocolonic involvement and penetrating phenotype in Crohn's disease appear to be rare. Nevertheless, other comorbidities are often present and IBD may contribute to a higher prevalence of laboratory abnormalities including anemia and vitamin D deficiency.